Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/sim.9176
|View full text |Cite
|
Sign up to set email alerts
|

Informing power and sample size calculations when using inverse probability of treatment weighting using the propensity score

Abstract: Propensity score weighting is increasingly being used in observational studies to estimate the effects of treatments. The use of such weights induces a within‐person homogeneity in outcomes that must be accounted for when estimating the variance of the estimated treatment effect. Knowledge of the variance inflation factor (VIF), which describes the extent to which the effective sample size has been reduced by weighting, allows for conducting sample size and power calculations for observational studies that use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Given the observational, exploratory nature of the study, and in the absence of a pre‐defined hypothesis, a sample size was not calculated a priori . A post‐hoc calculation of the power showed that this was greater than 80% for the primary outcome, according to the method by Austin based on calculation of the variance inflation factor (VIF), which describes the extent to which the effective sample size has been reduced by weighting 29 . The post‐hoc power of a chi‐square test for the observed difference in proportion of success at 3 months is 0.99, while VIF is 1.15 based on a c ‐statistics of the model equal to 0.67 and a prevalence of treatment equal to 0.6.…”
Section: Methodsmentioning
confidence: 99%
“…Given the observational, exploratory nature of the study, and in the absence of a pre‐defined hypothesis, a sample size was not calculated a priori . A post‐hoc calculation of the power showed that this was greater than 80% for the primary outcome, according to the method by Austin based on calculation of the variance inflation factor (VIF), which describes the extent to which the effective sample size has been reduced by weighting 29 . The post‐hoc power of a chi‐square test for the observed difference in proportion of success at 3 months is 0.99, while VIF is 1.15 based on a c ‐statistics of the model equal to 0.67 and a prevalence of treatment equal to 0.6.…”
Section: Methodsmentioning
confidence: 99%
“…Because there is no validated solution to estimate the required sample size or study power using the inverse propensity score-weighting method, we do not provide such estimates. 32…”
Section: Sample Size and Study Powermentioning
confidence: 99%
“…Finally, this study is limited by the estimated statistical power. Power analyses for propensity score weighting approaches are complex, and post hoc power analyses suggested the study may be underpowered (Austin, 2021); future research should be conducted with larger samples and comparison groups to better power analyses. 2…”
Section: Policy Implicationsmentioning
confidence: 99%
“… 2. Power was checked in two ways for this study: using the method suggested by Austin (2021) and using post hoc logistic regression models. Estimates calculated using logistic regression estimates suggested the analyses were sufficiently powered; however, these estimates are likely inaccurate, as they are estimates for traditional logistic regression models rather than propensity score approaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation